2010
DOI: 10.1213/ane.0b013e3181b5a292
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Anesthetic Potency in Aged Alzheimer Mice

Abstract: BACKGROUND The number of elderly patients with frank or incipient Alzheimer’s disease (AD) requiring surgery is growing as the population ages. General anesthesia may exacerbate symptoms of and the pathology underlying AD, so minimizing anesthetic exposure may be important. This requires knowledge of whether the continuing AD pathogenesis alters anesthetic potency. METHODS We determined the induction potency and emergence time for isoflurane, halothane, and sevoflurane using the minimum alveolar anesthetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
1
17
0
1
Order By: Relevance
“…We started the study with approximately equal numbers of mice in all groups (≥10), but had significant mortality in the DMSO- and dantrolene-treated groups when they underwent surgery for the Alzet pump replacement, primarily during the anesthetic induction. Excess mortality in this transgenic animal has been documented before [2]. This suggests that, given the loss of nearly the same number of vehicle and dantrolene treated animals, the 3xTg-AD mouse model may be more vulnerable to the effects of anesthesia.…”
mentioning
confidence: 67%
“…We started the study with approximately equal numbers of mice in all groups (≥10), but had significant mortality in the DMSO- and dantrolene-treated groups when they underwent surgery for the Alzet pump replacement, primarily during the anesthetic induction. Excess mortality in this transgenic animal has been documented before [2]. This suggests that, given the loss of nearly the same number of vehicle and dantrolene treated animals, the 3xTg-AD mouse model may be more vulnerable to the effects of anesthesia.…”
mentioning
confidence: 67%
“…1). Recent studies have shown different sensitivity of inhaled anesthetics in transgenic models of AD (Bianchi et al, 2010). We did not find any difference in anesthetic sensitivity in control and AD rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, this may be difficult, since the minimal alveolar concentration values for animal models of AD are increased relative to their non-AD counterparts. 59,60 Although a recent study did not find an association between depth of anesthesia and development of POCD, 61 further research is certainly needed. Use of regional anesthesia instead of general anesthesia has been suggested to avoid volatile anesthetic exposure.…”
Section: Do We Need To Change Clinical Practice?mentioning
confidence: 99%